Kinerja Koperasi PRIMKOPPOL Resor Gunung Kidul - Inaryu Melly Triyani Widodo; Bambang Sugeng Dwiyanto (Jurnal Maksipreneur, 2016)
Since 2006 the government of the Republic of Indonesia has awarded to cooperatives achievement. This study is a description of which is an analysis by taking a cooperative object "Primkoppol Resort Gunungkidul". The purpose of analysis is to determine whether the cooperative has met the criteria of cooperative achievement in 2012-2014 reviewed according to the Regulation of the Minister of Cooperatives, Small and Medium Enterprises in 2006 on Guidelines for Assessment of Cooperative Achievement/Cooperative Award. The analysis shows that "Primkoppol Resort Gunungkidul" cooperative in the period 2012-2014 includes performance categories good / fairly good because of the four aspects assessed scored 70.5 in 2012 and 69 respectively for 2013 and 2014. However, since there are still some elements of sub aspects are worth 0 (return on equity, net profit margin, curent ratio, accounts receivable turnover and employment) it can not be categorized based on the achievement of cooperative Ministerial Regulation No.06/Per/M.KUKM/V/2006, dated May 1, 2006